Influence of Resident Education in Correctly Diagnosing Extremity Soft Tissue Sarcoma. (18th April 2013) - Alamanda, Vignesh K.; Crosby, Samuel N.; Mathis, Shannon L.; Archer, Kristin R.; Terhune, Kyla P.; Holt, Ginger E.
Abstract : Background . One-third of all extremity soft tissue sarcomas are misdiagnosed and inappropriately excised without proper preoperative diagnosis and planning. This study aimed at examining the clinical judgment of residents in both general and orthopaedic surgery and at determining whether resident education plays a role in appropriately managing unknown soft tissue masses. Methods . A case-based survey was used to assess clinical decisions, practice patterns, and demographics. Aggregate response for all of the clinical cases by each respondent was correlated with the selections made for practice patterns and demographic data. Results . A total of 381 responses were returned. A higher percentage of respondents from the orthopaedic group (84.2%) noted having a dedicated STS rotation as compared to the general surgery group (35.8%) P < 0 . 001 . Depth, size, and location of the mass, rate of growth, and imaging characteristics were considered to be important factors. Each additional year of training resulted in 10% increased odds of selecting the correct clinical decision for both groups. Conclusion . Our study showed that current residents in both orthopaedic surgery and general surgery are able to appropriately identify patients with suspicious masses. Continuing education in sarcoma care should be implemented beyond the years of residency training.